Thermodynamic assessment of binary erythritol-xylitol phase diagram for phase change materials design. (March 2018) - Gunasekara, Saman Nimali; Mao, Huahai; Bigdeli, Sedigheh; Chiu, Justin NingWei; Martin, Viktoria
Abstract: Here, the erythritol-xylitol binary system was thermodynamically optimized based on available experimental phase equilibrium data, to explore compositions suitable as phase change materials (PCMs) for thermal energy storage (TES). A previous experimental study revealed that erythritol-xylitol was a partially isomorphous system with a eutectic. In the thermodynamic evaluation, the CALPHAD method was employed coupling the phase diagram and thermodynamic property information. There, both unary and binary systems' experimental data were taken into account, and all phases were described using the substitutional solution model. Finally, a self-consistent thermodynamic description for the erythritol-xylitol system was achieved. The calculated eutectic point is at 76.7 °C and 26.8 mol% erythritol, agreeing well with the experimental data. The calculated phase diagram better-verifies the systems' solidus and the solvus, disclosing the stable phase relations. Based on the Gibbs energy minimization, phase diagrams can be predicted for the binary and higher order systems, provided the component subsystems are thermodynamically assessed beforehand. In conclusion, to move forward beyond e.g. non-isomorphous simple eutectic systems, methods using Gibbs free energy minimization from a fundamental point-of-view such as CALPHAD are essential. Highlights: The erythritol-xylitol phase diagram is optimized for the first time using CALPHAD. Previous theoretical studies of the system were limited to simple eutectic systems. New experiments show erythritol-xylitol to contain a partially isomorphous eutectic. The calculated erythritol-xylitol eutectic is at 76.7 °C and 26.8 mol% Erythritol. Calculated eutectic agrees with experimental point at 77 °C and 27 mol% Erythritol.